EVALUASI PROGRAM PENANGANAN ANAK JALANAN OLEH DINAS SOSIAL PEMUDA DAN OLAHRAGA KOTA SEMARANG MELALUI RUMAH PERLINDUNGAN SOSIAL ANAK (RPSA) PELANGI - Faradisa, Rosiana; Rostyaningsih, Dewi; Lituhayu, Dyah (Journal of Public Policy and Management Review, 2015)
Program of street children handling in Semarang city is based on the mayor’s decree no. 462/133 of 2002 which is about the formation of the coordinating social problem’s team. Street children handling program in this research through cooperation with Pelangi shelter. The purpose of the program is to preventing the child to stop doing the activity in the street. The evaluation models are used is the Single Program After-Only by Finterbusch and Motz. Evaluation of this program to see the result on street children handling programs will be viewed using criteria-criteria evaluation of policies according to Dunn are: effectiveness, efficiency, sufficiency, alignment, responsiveness, and accuracy. The barriers program that is viewed with achievement of each program according to the evaluation criteria of the policy by Dunn. Street children handling program result by Social, Youth and Sport Services of Semarang City through Pelangi shelter where in this criteria evaluation, there are still five criterias judged not good, based on the effectiveness, efficiency, sufficiency, alignment, and responsiveness. On the accuracy activities is considered good. Barriers to programs such as lack of commitment from the Social, Youth and Sport Services of Semarang city and the Pelangi shelter making activity stalled in the middle of the road. Lack of mentoring and controlling is also a barrier to factor in this program.Overall many judgment that haven’t been good on these evaluation criteria, then program which have run not been expressed successfully. Recommendations of this program, such as strengthening strategy and commitment of program implementor, assessment in detail on the balance between the time required and the volume of the service recipient, and continued assistance who receive benefits from the program.